Left ventricular mass and incident chronic kidney disease - Agarwal, Rajiv (Hypertension, 2020)
Chronic kidney disease (CKD) is associated with incident cardiovascular morbidity and mortality. Whether subclinical cardiovascular disease and target organ damage is associated with incident CKD is unknown. We investigated the relations of echocardiographic left ventricular (LV) mass with incident CKD. We evaluated 2258 Framingham Offspring cohort participants (mean age 57, 56% women) who underwent echocardiography at a routine examination and had an estimated glomerular filtration rate (eGFR) ≥60 mL/min/1.73m(2). We used Cox proportional-hazards regression with discrete time intervals to relate sex-standardized LV mass (independent variable) to the incidence of CKD, defined as eGFR <60 L/min/1.73m(2), on follow-up. During a median follow-up of 14.6 years, 373 (16.5%) participants developed incident CKD. Higher LVM was associated with higher risk of CKD after adjusting for prevalent CVD, body mass index, systolic blood pressure, total and HDL cholesterol, anti-hypertensive medication, smoking and diabetes, (HR) and 95% confidence interval 1.15 (95% CI 1.03–1.29, p<=0.017) per 1 standard deviation (SD) increase in LV mass g/m(2). Further adjustment for baseline eGFR (aHR 1.16 (95% CI 1.04 – 1.31, p=0.010) and baseline urine albumin/creatinine ratio (aHR 1.18 (95% CI 1.04 – 1.33, p=0.009) slightly attenuated the association. In our community-based sample, LV mass was associated with incident CKD prospectively, which suggests that the relations between CKD and subclinical cardiovascular disease may be bidirectional. Further studies are needed to confirm our findings.